Platelet-Rich Fibrin Used as a Scaffold in Pulp Regeneration: Case Series - Selin Şen; Ceren Çimen; Elif Şenay; Tuğba Bezgin (Cumhuriyet University, 2021)
Regenerative endodontic treatment (RET) is a biologically based treatment approach to provide root development and increase the prognosis of teeth. The purpose of this case series was to evaluate the clinical and radiological results of RET using platelet-rich fibrin (PRF), in 4 immature teeth with necrotic pulps. At the end of 18-24-month follow-up, no clinical symptoms were recorded. Apical closure was observed in 3 of the 4 teeth. All of the preoperative periapical lesions were healed. However, a calcified tissue formed in the middle third of the root in one case diagnosed with chronic apical periodontitis at 3-month follow-up. PRF was successful as a scaffold and can be recommended for revascularization protocol of necrotic immature teeth. However, prognosis of tooth can be attributed to many factors such as duration of pulp necrosis, pretreatment status of the periapical region and viability of living tissues.